2015
DOI: 10.4236/jbm.2015.36004
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of the Symbiotic Bacteria Associated with Toxic Marine Dinoflagellate Alexandrium tamarense

Abstract: Paralytic shellfish poisoning (PSP) toxins are potent neurotoxins mainly produced by dinoflagellates and being concentrated in bivalves through food web transfer. Increasing number of findings of toxin-producing bacteria in the cells of dinoflagellate such as Alexandriumtamarense supports the hypothesis of the bacterial origin of PSP toxins. Evidence that there are specific symbiosis bacterial taxa associated with the phytoplankton indicates the presence of specific selective mechanisms between them, and impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 12 publications
0
44
0
Order By: Relevance
“…The diversity and community structure of bacteria and fungi were assessed using high‐throughput sequencing analysis of the 16S rRNA gene within the V3–V4 hypervariable region and the 18S rRNA gene within the ITS regions. These assessments were carried out by Beijing Auwigene Tech, Ltd. (Beijing, China) using the Illumina Miseq PE300 sequencing platform (Illumina, Inc., San Diego, CA, USA) according to the manufacturer's recommendations using the universal primers 338F/806R (bacteria, ACTCCTACGGGAGGCAGCAG/GGACTACHVGGGTWT CTAAT) (Zhang et al., ) and ITS1‐F/ITS2 (fungi, CTTGGTCATTTAGAGGAAGT/TGCGTTCTT CATCGATGC) (Peters, Wu, Hayes, & Ahn, ). Raw sequences were processed using the pipeline tools QIIME (Caporaso et al., ) and MOTHUR (Schloss et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…The diversity and community structure of bacteria and fungi were assessed using high‐throughput sequencing analysis of the 16S rRNA gene within the V3–V4 hypervariable region and the 18S rRNA gene within the ITS regions. These assessments were carried out by Beijing Auwigene Tech, Ltd. (Beijing, China) using the Illumina Miseq PE300 sequencing platform (Illumina, Inc., San Diego, CA, USA) according to the manufacturer's recommendations using the universal primers 338F/806R (bacteria, ACTCCTACGGGAGGCAGCAG/GGACTACHVGGGTWT CTAAT) (Zhang et al., ) and ITS1‐F/ITS2 (fungi, CTTGGTCATTTAGAGGAAGT/TGCGTTCTT CATCGATGC) (Peters, Wu, Hayes, & Ahn, ). Raw sequences were processed using the pipeline tools QIIME (Caporaso et al., ) and MOTHUR (Schloss et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Metagenomic approaches already revealed that dinoflagellates' phycosphere is heavily colonized by bacteria [103]. Several studies have been done to investigate bacteria-dinoflagellates association especially in terms of toxin production, dinoflagellates' mortality and nutrient exchange [104][105][106].…”
Section: Symbiosismentioning
confidence: 99%
“…There is also increasing evidence that there are specific symbiosis bacterial taxa associated with phytoplankton, indicating the presence of specific selective mechanisms, and implying that the symbiosis bacteria have some functions to the benefit of the alga, and these interactions could be the product of co-evolution between bacteria and algae over millions of years (Dantzer WR . Currently culture-independent highthroughput pyrosequencing analysis is able to provide a thorough description of microbiota community in environmental samples, which also helps to reveal their potential function (McCann JC et al 2014, Zhang XL et al 2015). This paper is aimed to demonstrate the biodiversity of the intracellular bacteria closely associated with toxic PSP-producing dinoflagellate, Alexandrium tamarense and Alexandrium minutum, using pyrosequencing method.…”
Section: Introductionmentioning
confidence: 99%